Personification of Russia in the 18th-Century Art: The Idea and Its Visualization - Chebakova, Polina A.; Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2022)
The paper reveals and systematizes the key features of personification of Russia in the 18th-century fine art in the context of her textual descriptions and European iconography. Alongside with conventional female figure representing the country, it examines cases when, in compositions celebrating peace treaties, Russia is embodied in male guise as well as the cases of depiction of Russia as a baby, which is rooted in European tradition of glorifying newly-born heir for the throne as infant Hercules strangling serpents. The most stable features of personification of Russia (her most usual attributes, namely crown and coat-of-arms) point to monarchial rule of the state and distinguish it among others. The main means of characterization are gestures, the meaning of which in all variations is to demonstrate Russia’s obedience to the ruler. Other ideas are visualized either by situational attributes or other allegorical figures represented in the composition. The age, physical and facial features of the personification of Russia in both fine arts and poetry almost always gravitate to vague ideal, the costume is a variation of an ancient one. The more significant are the rare exceptions which are examined in the article.The reported study was funded by the Russian Science Foundation, project number 21-78-00067 URL: https://rscf.ru/project/21-78-00067/.
Keywords: 18th-century Russian art; personification of Russia; conventions of European art schools; national costume; fireworks; love for the Fatherland; Francesco Fontebasso